Catalytic steam reforming and heat sink of high-energy-density fuels: Correlation of reaction behaviors with molecular structures. (15th February 2021) - Zheng, Qiancheng; Xiao, Zhourong; Xu, Jisheng; Pan, Lun; Zhang, Xiangwen; Zou, Ji-Jun
Graphical abstract: Highlights: Catalytic steam reforming of high-energy–density (HED) fuels was investigated. Steam reforming reaction can significantly improve the heat sink of HED fuels. The effects of H/C and (H/C)*M a on steam reforming reactivity were studied. Abstract: This work investigated the steam reforming (SR) performance of high-energy–density (HED) fuels including exo- tetrahydrodicyclopentadiene ( exo -THD), exo -tetrahydrotricyclopentadiene ( exo -THT), 1, 3-dimethyladamantane (DMA) and quadricyclane (QC), aiming to provide sufficient heat sink for hypersonic flight. The fuel conversion decreases in the order of QC > DMA ≈ exo -THD >  exo -THT, while the molecular-structure-dependent catalyst stability trend is DMA >  exo -THD > QC ≈ exo -THT, which are related to the H/C value, carbon deposition and exposure of active Ni species after carbon deposition. Importantly, the catalytic SR reaction can significantly improve the total heat sink of HED fuels. Especially, DMA and exo -THD with higher H/C and (H/C)*M a exhibit excellent performance on activity and stability, on which high total heat sink, total heating value and coke-resistance are achieved. This work provides the molecule-SR heat sink relationship for the design of the effective cooling system for the hypersonic flight.